2015
DOI: 10.1148/radiol.14140283
|View full text |Cite
|
Sign up to set email alerts
|

Luminal-Type Breast Cancer: Correlation of Apparent Diffusion Coefficients with the Ki-67 Labeling Index

Abstract: Considering convenience for routine practice, the authors suggest that the mean ADC apparent diffusion coefficient of the conventional method would be practical to use for estimating the Ki-67 labeling index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
85
7

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(115 citation statements)
references
References 33 publications
18
85
7
Order By: Relevance
“…34 Studies have demonstrated that high expression of Ki-67 indicates a high aggressiveness, a high risk of relapse, and a poor prognosis 15,35,36 ; a low ADC value suggests high proliferative activity and consequently a malignant tumor. 37,38 Our study showed similar results. A significant difference in ADC value was found between ESSs with the positive and negative Ki-67 expression.…”
Section: Discussionsupporting
confidence: 83%
“…34 Studies have demonstrated that high expression of Ki-67 indicates a high aggressiveness, a high risk of relapse, and a poor prognosis 15,35,36 ; a low ADC value suggests high proliferative activity and consequently a malignant tumor. 37,38 Our study showed similar results. A significant difference in ADC value was found between ESSs with the positive and negative Ki-67 expression.…”
Section: Discussionsupporting
confidence: 83%
“…We recently reported that tumours with a high Ki-67 labelling index showed lower ADC values than those with a low Ki-67 labelling index in luminal-type breast cancer NOS [24]. LVI was reported to associate with tumours with a high cell proliferation level or high Ki-67 labelling index [27], which are likely to have lower ADC values.…”
Section: Discussionmentioning
confidence: 96%
“…2b). We recorded the mean ADC value as the tumour-ADC on the basis of the recent study revealing that the mean value of an as-large-aspossible round or oval ROI inside the tumour correlated with a Ki-67 labelling index in luminal-type breast cancer NOS diagnosed by biopsy [24].…”
Section: Image Interpretationmentioning
confidence: 99%
“…Within invasive disease, a number of studies have shown ADC values to negatively correlate with tumor grade [1721]. A similar correlation was seen with tumor proliferation, using Ki-67 index as a marker [13, 2126]. The ability to detect more aggressive tumors may aid in consideration of neoadjuvant treatment prior to surgery.…”
Section: Clinical Applicationsmentioning
confidence: 94%